A Systematic Review of EFL Students' Self-Efficacy in The Learning Context - Gunawan, Gunawan; Rizky, Muh. Faizal; Wulandari, Samian (Naifaderu Cipta Sejahtera, 2024)
Purpose This study reviews the empirical literature on self-efficacy, a central concept in self-efficacy theory. Methodology A comprehensive review spanning from 2013 to 2023 was conducted, focusing on the impact of student learning. The review analyzed 25 scholarly articles on student self-efficacy within the context of learning. Results/Findings The findings demonstrate positive correlations among student self-efficacy, engagement, pedagogy, classroom instruction, student experiences, and teaching strategies. The literature review categorized publications into two main themes: the effects of self-efficacy and factors influencing self-efficacy in learning environments. The study concludes that various factors enhance students' perceptions of their capabilities in the classroom, which strongly predicts their performance across language-related tasks. Implications The study underscores the critical role of student self-efficacy in learning and its potential for future improvement